1992
DOI: 10.1364/ao.31.000909
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modeling studies of organic compact disk-writable media

Abstract: The marking response of optical data storage structures is controlled by the interplay of optical and thermal effects. Relatively simple analytical expressions were derived that provided a qualitative and semiquantitative description of the optical and thermal characteristics of an organic dye-based optical recording medium. These were used to explain various phenomena that were observed during recording experiments that were performed on compact disk-writable media and to evolve a new understanding of the mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Significant insights can be achieved, however, by investigation of the recorded regions with different microscopic techniques [35][36][37][38] and the assistance of model calculations. [41][42][43] As already discussed, the exact development of the bump in the polycarbonate and the destruction of the dye are pivotal for CNR and jitter. It follows from this that the first requirement is that the decomposition point of the dye must lie far enough above the glass transition point of the polycarbonate that the polycarbonate melts during recording.…”
Section: Thermal Properties Of the Dye Layermentioning
confidence: 89%
“…Significant insights can be achieved, however, by investigation of the recorded regions with different microscopic techniques [35][36][37][38] and the assistance of model calculations. [41][42][43] As already discussed, the exact development of the bump in the polycarbonate and the destruction of the dye are pivotal for CNR and jitter. It follows from this that the first requirement is that the decomposition point of the dye must lie far enough above the glass transition point of the polycarbonate that the polycarbonate melts during recording.…”
Section: Thermal Properties Of the Dye Layermentioning
confidence: 89%
“…Dabei entzieht sich der Schreibprozess selbst der direkten experimentellen Beobachtung. Durch die Untersuchung der beschriebenen Bereiche mit verschiedenen Mikroskopietechniken [35][36][37][38] und mithilfe von Modellrechnungen [41][42][43] lassen sich dennoch wichtige Informationen gewinnen. Wie bereits dargestellt, sind für CNR und Jitter die exakte Ausbildung der Beule im Polycarbonat und die Zersetzung des Farbstoffes entscheidend.…”
Section: Thermische Eigenschaften Der Farbstoffschichtunclassified
“…When excited dye molecules are able to overcome the viscosity (potential) barrier, the transformation takes place. Evans [3] and Bartholomeusz [4] reported that a polymer matrix subjected to 10 mW of laser power can reach 25O C in less than 200 ns. This indicates that polymer media can easily be heated to softening temperature Tg in a very short time.…”
Section: Materials Writinglerase Speed-fundamental Limitmentioning
confidence: 99%